2020
DOI: 10.1108/jpbafm-08-2019-0119
|View full text |Cite
|
Sign up to set email alerts
|

Budgetary practices in a Tanzanian University: Bourdieu's theory

Abstract: PurposeThis paper explores budgetary practices in a Tanzanian university after decentralization.MethodologyData were collected through interviews, document analysis, and observation. Moreover, Bourdieu's theory was used in open and axial coding procedures for data analysis.FindingsThe findings show that decentralized budgeting was a disillusionment. Administrators failed to transfer financial authority to resource recipients. Budgetary practices were shaped by the social structure/budget cycle (field), resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…More recently, this trend has also expanded into the East, the Middle East and Africa (e.g. Harun et al , 2020; Komutputipong and Keerasuntonpong, 2019; Upping and Oliver, 2012; Mah'd, 2020; Mkasiwa, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, this trend has also expanded into the East, the Middle East and Africa (e.g. Harun et al , 2020; Komutputipong and Keerasuntonpong, 2019; Upping and Oliver, 2012; Mah'd, 2020; Mkasiwa, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Current budgeting research has mostly employed Bourdieu's theory (see, e.g. Mkasiwa, 2020), negotiated order and power (Lapsley et al, 2011), political budget cycle theory (K€ onig and Wenzelburger, 2017), institutional (logics) theory (Ezzamel et al, 2012;Kaufman and Covaleski, 2019) and dramaturgy (Corrigan, 2018). Contingency theory of change (Leavitt, 1972) while extensively applied in management accounting (Hayes, 1977;Otley, 1980) is relatively absent in budgeting-specific research.…”
Section: Jpbafm 353mentioning
confidence: 99%
“…Current budgeting research has mostly employed Bourdieu's theory (see, e.g. Mkasiwa, 2020), negotiated order and power (Lapsley et al. , 2011), political budget cycle theory (König and Wenzelburger, 2017), institutional (logics) theory (Ezzamel et al.…”
Section: Contingency Theorymentioning
confidence: 99%
“…Over the last 30 years, institutional and socioeconomic development and globalization have played crucial roles in the changes observed in the higher education sector. These changes have affected aspects such as governance (Boitier and Rivi ere, 2013), accountability (Narayan et al, 2017), reputation (Suomi et al, 2014), higher education export (Guthrie et al, 2014), organization, funding, management (Tucker and Parker, 2020), budgeting (Lepori and Montauti, 2020;Mkasiwa, 2020), accounting systems (Conrath-Hargreaves and W€ ustemann, 2019;Moll and Hoque, 2011), research assessment (Martin-Sardesai et al, 2017a), as well as universities' academic and social legitimacy (Gebreiter and Hidayah, 2019). Previous studies have also shown clear changes occurring in the performance measurement (PM) of universities.…”
Section: Introductionmentioning
confidence: 99%